-6x-8(x+7)=

Simple and best practice solution for -6x-8(x+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-8(x+7)= equation:


Simplifying
-6x + -8(x + 7) = 0

Reorder the terms:
-6x + -8(7 + x) = 0
-6x + (7 * -8 + x * -8) = 0
-6x + (-56 + -8x) = 0

Reorder the terms:
-56 + -6x + -8x = 0

Combine like terms: -6x + -8x = -14x
-56 + -14x = 0

Solving
-56 + -14x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + -14x = 0 + 56

Combine like terms: -56 + 56 = 0
0 + -14x = 0 + 56
-14x = 0 + 56

Combine like terms: 0 + 56 = 56
-14x = 56

Divide each side by '-14'.
x = -4

Simplifying
x = -4

See similar equations:

| -7+3(1+5v)= | | 9+6a=57 | | 6-9x=5x-10x+14 | | 6x-3=3x+5 | | 2+(4/a)=(14/a)-3 | | sqrt(x+1)+sqrt(2x)=sqrt(5x+3) | | -2(n-7)+2n= | | 50-3x=4 | | 2x(y+2)+4(y+2)=0 | | 5x+9=3x+5 | | 2rs-8r+5s-7rs+12r-5s= | | A=5b+2 | | 15y+1=4 | | ln(x^2+5x)=0 | | 10x^2-3x+2=0 | | 9(y-8)=8y-8 | | -7v+35=-4(v-5) | | x/9-7=-2 | | a/a-(a/2)= | | 5x^2+x+25x+25=0 | | x^3+6x^2+10x= | | -3.4x=9 | | -7x-5x+2=22 | | 16x^3+16x^2=3x | | 70-I=61 | | 6-2x(3x-1)=2 | | 3x+4y+6=30 | | Inx+ln(x-2)=5 | | 6y-(2x)=0 | | 6(x-7)=8x-34 | | t/6-8=13 | | F(x)=tan^3(4x+1) |

Equations solver categories